Relationship Between Exclusive Breastfeeding and Birth Weight (BBL) to The Incidence of Respiratory Tract Diseases in Children at PKU Gamping Hospital - Gina Puspita; Kalya Hasana (CV. Inara, 2026)
Background: Exclusive breastfeeding during the first six months plays an important role in fulfilling nutritional needs and strengthening children's immunity against infections. However, exclusive breastfeeding coverage in Indonesia remains below the national target. Infants with abnormal birth weight are also more susceptible to infections, including respiratory tract diseases. Objective: To analyze the relationship between exclusive breastfeeding and birth weight with respiratory tract diseases among children at PKU Gamping Hospital. Methods: This analytical observational study used a cross-sectional design involving children aged 18 months to 5 years who visited the pediatric clinic of PKU Gamping Hospital from May to July 2025. A total of 86 children were selected using purposive sampling. Data were collected through questionnaires and analyzed using the chi-square test with a significance level of p<0.05. Results: Among 86 children, 53.5% were male and 46.5% female. Exclusive breastfeeding was significantly associated with respiratory diseases in children (p=0.017), while birth weight showed no significant association (p=0.202). Conclusion: Exclusive breastfeeding is significantly associated with respiratory diseases in children, whereas birth weight is not significantly associated.